( 3xy+2x-3x+4x²y-7x²) 3xy
Soluções para a tarefa
Respondido por
0
3xy * 3xy = 9x²y²
2x * 3xy = 6x²y
3x * 3xy = 9x²y
4x²y * 3xy = 12x³y²
7x² * 3xy = 21x³y
reescrevendo
9x²y² + 6x²y - 9x²y + 12x³y² - 21x³y =
9x²y²- 3x²y + 12x³y² - 21x³y ***
2x * 3xy = 6x²y
3x * 3xy = 9x²y
4x²y * 3xy = 12x³y²
7x² * 3xy = 21x³y
reescrevendo
9x²y² + 6x²y - 9x²y + 12x³y² - 21x³y =
9x²y²- 3x²y + 12x³y² - 21x³y ***
Perguntas interessantes
Português,
11 meses atrás
História,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás